(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Samalyuk A. A. Trends in local history education in the content of methodological recommendations for teachers of secondary schools for the purposes of formation of creative activity of basic school students in the tourism and local history work. The article reveals trends in local history education as a component of the Natural History of Education. Proved that mastering local history materіalom sposobostvuet enhance creativity among elementary school students in the process se-tourist local history work.